Associations of insulin resistance and inflammatory biomarkers with endometrial cancer survival: The Alberta endometrial cancer cohort study. (16th February 2022) - Morielli, Andria R.; Kokts‐Porietis, Renée L.; Benham, Jamie L.; McNeil, Jessica; Cook, Linda S.; Courneya, Kerry S.; Friedenreich, Christine M.
Abstract: Background: Metabolic dysfunction and inflammation have been associated with endometrial cancer risk; however, their influence on endometrial cancer survival is less understood. Methods: A prospective cohort study of 540 endometrial cancer cases diagnosed between 2002 and 2006 in Alberta were followed for survival outcomes to 2019. Baseline blood samples collected either pre‐ or post‐hysterectomy were analyzed for glucose, insulin, adiponectin, leptin, tumor necrosis factor‐α, interleukin‐6, and C‐reactive protein. Covariates were obtained during in‐person interviews and via medical chart abstraction. Cox proportional hazard regression models were used to estimate multivariable‐adjusted hazard ratios (HR) and 95% confidence intervals (95% CI) for the association between each biomarker and disease‐free and overall survival. Results: Blood samples were collected from 520 of the 540 participants (presurgical n = 235; postsurgical n = 285). During the median follow‐up of 14.3 years (range 0.4–16.5 years), there were 125 recurrences, progressions, and/or deaths with 106 overall deaths. None of the biomarkers were associated with disease‐free or overall survival in multivariable‐adjusted analyses. In an exploratory stratified analysis, the highest level of presurgical adiponectin, compared to the lowest level, was associated with improved disease‐free (HR = 0.42, 95% CI = 0.20–0.85) and overall (HR = 0.41, 95% CI = 0.18–0.92) survival, whereas no statistically significant associations were noted for postsurgical measures of adiponectin. Conclusions: Overall, there was no evidence of an association between biomarkers of insulin resistance and inflammation with mortality outcomes in endometrial cancer survivors. Future cohort studies with serial blood samples are needed to understand the impact of changes in insulin resistance and inflammatory markers on endometrial cancer survival. Abstract : The Alberta Endometrial Cancer Cohort Study prospectively examined the association between biomarkers of insulin resistance and inflammation with survival outcomes in 540 incident endometrial cancer cases ascertained through the Alberta Cancer Registry between 2002 and 2006. Shortly after their cancer diagnosis, participants provided an 8‐hour fasting blood sample and completed in‐person interviews during which detailed demographic, medical and lifestyle information was collected. Clinical data were abstracted from medical records and vital status was obtained by the Alberta Cancer Registry through data linkage with Vital Statistics Alberta and Statistics Canada to 2019.